Morphometric Study Of Distal End Femur In The Population Of J&K : It’s Clinical Implication In Knee Joint Prostheses. - Dr Rahul sharma , Dr Abhilasha maharshi , Dr kewal Kishore Thakur (Cuestiones de Fisioterapia, 2025)
Background: Knee joint is a complex joint which includes both tibiofemoral joint and patellofemoral joint. Thebony geometry of the tibia and femur contributes to the static stability of the knee joint and is responsible forthe normal knee kinematics. The distal extremity of the femur is wider and presents a widely expanded doublecondyle bearing partly articular surface for transmission of weight to the tibia.Objective: to study morphometric study of distal end femur in the population of central india : comparison withother ethnic groups and it’s clinical implication in knee joint prostheses.